A novel TDMA-based MAC protocol for mobile in-vivo body sensor networks - Lin, Lin (2013)
With the development of sensor and wireless communication technologies, the concept of body sensor networks (BSNs) is proposed in recent years. BSNs are used to measure a large number of vital signs of the human body. Body sensor devices are typically powered by batteries and difficult to replace, so energy efficient medium access control (MAC) protocols, which can perform medium access mechanism with less energy are necessary. In this paper, we propose a novel energy saving MAC protocol for mobile BSNs based on time division multiple access (TDMA). An uplink, downlink asymmetric network architecture is introduced. A changeable access and sleep frame format as well as a routing algorithm are proposed. Simulation results show that the proposed MAC protocol achieves lower energy consumption than IEEE 802.15.6.